Design of an NPK Fertilizer Pelletizer: Pelletizer (Nigerian Journal of Technology, 2021)
Fertilizer application to boost crop yield has become inevitable and can be a source of environmental concern. In this study, the design of simple pelletizing equipment was considered to process fertilizer powder into pellets. This equipment was designed to convey, compact and extrude the NPK compound via a screw conveyor, through a die and into pellets. On the basis of the size of this home-made system and the bulk density of inorganic NPK compounds, a 1492 watts (2hp) motor and a 25mm diameter shaft of screw conveyor was used to convey the NPK compound at a rate of 3.0m3/h, and then compacted and extruded it into pellets. The octahedral shear stress failure criterion helped to determine how well the pelleting pressure chamber designed with mild steel, holds up against the radial (σr), hoop (σh) and axial (σz) stresses generated which amounted to an octahedral shear stress (σoct) of 1.5N/mm2,  which is well below the yield stress of mild steel. The use of this equipment to produce inorganic NPK compounds into pellets helps improve fertilizer use efficiency and also militates against the environmental challenges posed by NPK fertilizer usage